UPAYA PENINGKATAN HASIL BELAJAR ILMU PENGETAHUAN SOSIAL DENGAN PEMBELAJARAN KOOPERATIF TIPE TPS (THINK PAIR SHARE) PADA KELAS IV SD NEGERI 001 UKUI SATU - Asnimar ' (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar Fakultas Keguruan dan Ilmu Pendidikan Universitas Riau, 2017)
This research was motivated by the activity and motivation of students to learn social sciences is still low. This is shown in their behavior when the following study social sciences. Based on the test scores of the first half of social sciences with KKM (minimum completeness criteria) was 65 known that 58% of students have graduated KKM while 42% of students did not complete. Under the conditions described, we can conclude that student learning outcomes are still low. Researchers also conducted interviews with several students. Some students said that the conditions were not conducive classes, friends who like crowded in the classroom, the way teachers deliver material is less clear, the reason for the lazy student learning so that learning is low. The objectives to be achieved in this research is to determine the application of cooperative learning think pair share (TPS) in improving learning outcomes for social sciences at the fourth grade students of SD Negeri 001 Ukui Satu. lessons classroom action research (PTK) planned two cycle. Each cycle in action research consists of four stages, namely: 1) planning (planning), 2) the implementation of the (acting), 3) of observation (observing), 4) reflection (reflecting). This study was conducted in SD Negeri 001 Ukui Satu in the fourth grade, while the timing of this research is in the second semester of the academic year 2016. In this classroom action research that is the subject of research is the students of class IV consisting of 34 students with a composition of 11 male students-Eighteen and 23 female students. Data collection techniques in this study is the observation, testing, documentation and interviews.